Cargo proteins of plasma astrocyte‐derived exosomes in Alzheimer's disease. Issue 11 (10th August 2016) - Goetzl, Edward J.; Mustapic, Maja; Kapogiannis, Dimitrios; Eitan, Erez; Lobach, Irina V.; Goetzl, Laura; Schwartz, Janice B.; Miller, Bruce L.
ABSTRACT: Efficient intercellular transfer of RNAs, proteins, and lipids as protected exosomal cargo has been demonstrated in the CNS, but distinct physiologic and pathologic roles have not been well defined for this pathway. The capacity to isolate immunochemically human plasma neuron‐derived exosomes (NDEs), containing neuronspecific cargo, has permitted characterization of CNS‐derived exosomes in living humans. Constituents of the amyloid β‐peptide (Aβ)42‐generating system now are examined in 2 distinct sets of human neural cells by quantification in astrocyte‐derived exosomes (ADEs) and NDEs, enriched separately from plasmas of patients with Alzheimer's disease (AD) or frontotemporal dementia (FTD) andmatched cognitively normal controls. ADE levels of β‐site amyloid precursor protein‐cleaving enzyme 1 (BACE‐1), γ‐secretase, soluble Aβ42, soluble amyloid precursor protein (sAPP)β, sAPPα, glial‐derived neurotrophic factor (GDNF), P‐T181‐tau, and P‐S396‐tau were significantly (3‐ to 20‐fold) higher than levels in NDEs for patients and controls. BACE‐1 levels also were a mean of 7‐fold higher in ADEs than in NDEs from cultured rat type‐specific neural cells. Levels of BACE‐1 and sAPPβ were significantly higher and of GDNF significantly lower in ADEs of patients with AD than in those of controls, but not significantly different in patients with FTD than in controls. Abundant proteins of the Aβ42 peptide‐generating system in ADEs may sustain levels in neurons. ADE cargo proteins may be useful for studies of mechanisms of cellular interactions and effects of BACE‐1 inhibitors in AD.—Goetzl, E. J., Mustapic, M., Kapogiannis, D., Eitan, E., Lobach, I. V., Goetzl, L., Schwartz, J. B., Miller, B. L. Cargo proteins of plasma astrocyte‐derived exosomes in Alzheimer's disease. FASEB J. 30, 3853–3859 (2016) www.fasebj.org